2017
DOI: 10.1016/j.bpsc.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Gamma-Aminobutyric Acid Concentrations Are Associated With Cognitive Performance in Older Adults

Abstract: BACKGROUND Gamma-aminobutyric acid (GABA), the brain’s principal inhibitory neurotransmitter, has been associated with perceptual and attentional functioning. Recent application of magnetic resonance spectroscopy (MRS) provides in vivo evidence for decreasing GABA concentrations during adulthood. It is unclear, however, how age-related decrements in cerebral GABA concentrations contribute to cognitive decline, or whether previously reported declines in cerebral GABA concentrations persist during healthy aging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
152
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(169 citation statements)
references
References 49 publications
12
152
4
1
Order By: Relevance
“…Specifically, GABA+/Cr levels in frontal and parietal brain regions have been shown to decrease with age (2). This finding was subsequently replicated in comparable voxel locations (3) and was associated with age-related changes in cognitive performance. Cognitive performance was strongly correlated with frontal GABA+ concentrations, even after accounting for age, the fraction of cerebral spinal fluid (CSF) in the MRS voxel (a coarse measure of brain atrophy) and behavioral factors such as education or age related normative performance.…”
Section: Introductionmentioning
confidence: 62%
“…Specifically, GABA+/Cr levels in frontal and parietal brain regions have been shown to decrease with age (2). This finding was subsequently replicated in comparable voxel locations (3) and was associated with age-related changes in cognitive performance. Cognitive performance was strongly correlated with frontal GABA+ concentrations, even after accounting for age, the fraction of cerebral spinal fluid (CSF) in the MRS voxel (a coarse measure of brain atrophy) and behavioral factors such as education or age related normative performance.…”
Section: Introductionmentioning
confidence: 62%
“…During brain aging, the fidelity of neuronal network activity within and between brain regions is perturbed, in some individuals relatively subtly and in others pathologically. Excitatory imbalances occur in the aging brain as a result of impaired GABAergic signaling, particularly reduced signaling via GABA-A receptors (Heise et al, 2013; Richardson et al, 2013; McQuail et al, 2015; Porges et al, 2017). Several hallmarks of brain aging can render neuronal circuits vulnerable to hyperexcitability and excitotoxic damage, including oxidative stress, mitochondrial dysfunction, impaired adaptive stress responses, and inflammation (Camandola and Mattson, 2011).…”
Section: Cellular and Molecular Hallmarks Of Brain Agingmentioning
confidence: 99%
“…Recent studies showed that such reductions of GABA levels in the human brain are associated with cognitive impairments in an age-dependent manner [8] and are further worsened during older age [9]. …”
Section: Introductionmentioning
confidence: 99%